Investigation of the frequency and causes of injuries in football players - Akcan, Firat (Progress in Nutrition, 2021)
Study Objectives: Football, by its nature, is a sport in which physical struggle is very intense and in which related injuries can occur. It is thought that it may be useful to know what injuries occur in amateur football players and why they occur. The aim of this study is to investigate the frequency and causes of injuries seen in male athletes playing football in amateur sports clubs in Gaziantep. Methods: A total of 200 athletes from the super amateur league (n: 16), amateur (n: 45), U19 (n: 69), U17 (n: 16) and other leagues (n: 54) were included in the study on a voluntary basis. Survey model was used in this study. The Sports Injuries Questionnaire developed by Yıldız was applied to the athletes. A chi-square test was used to compare the participants’ personal characteristics. Results: A statistically significant association (p<0.05) was found between players’ exposure to injury and the variables of players’ age, classification and position. Conclusion: In conclusion, it has been found that most of the injuries of football players occur in the second half of the game; these injuries occur as cramps, sprains, cracks or fractures, muscle crushes or muscle tears, and field floor increases the risk of injury. It has been concluded that injuries in amateur football players are caused by decreased fitness, unsuitable football grounds and advanced age.